Deneys Reitz and the First World War: An Introduction to the Department of Defence Archival Holdings - Kleynhans, Evert (Scientia Militaria - South African Journal of Military Studies, 2017)
The historical sources detailing South Africa’s participation in the First World War are vast, and range from official publications to regimental histories, private diaries and first-hand accounts. The Department of Defence (DOD) Documentation Centre is the custodian of all military archival material generated since the inception of the Department on 1 July 1912. Nonetheless, the material in the repository remains underutilised, despite the number of researchers who have worked or those who are now working on the military history of the Union Defence Force (UDF) during the Afrikaner Rebellion, as well as the campaigns fought in German South West Africa (GSWA), German East Africa (GEA), the Middle East and Europe. The centennial commemoration of the First World War gave rise to an increase in both professional and amateur military historical research, and a resurgence in First World War studies globally. A large number of researchers are expected to consult the First World War material at the Documentation Centre. An increase in interest in a variety of themes relating to South Africa and South African participation in the war is already detected. This article reports on a review of the Documentation Centre’s First World War holdings in relation to South Africa’s participation in the war by using Deneys Reitz, of Commando fame as a lens to illustrate the range of information available to researchers.